Does Hypothyroidism Affect Gastrointestinal Motility? - Olga Yaylali; Suna Kirac; Mustafa Yilmaz; Fulya Akin; Dogangun Yuksel; Nese Demirkan; Beyza Akdag (Gastroenterology Research and Practice)
Background. Gastrointestinal motility and serum thyroid hormone levels are closely related. Our aim was to analyze whether there is a disorder in esophagogastric motor functions as a result of hypothyroidism. Materials and Methods. The study group included 30 females (mean age ± SE 45.17 ± 2.07 years) with primary hypothyroidism and 10 healthy females (mean age ± SE 39.40 ± 3.95 years). All cases underwent esophagogastric endoscopy and scintigraphy. For esophageal scintigraphy, dynamic imaging of esophagus motility protocol, and for gastric emptying scintigraphy, anterior static gastric images were acquired. Results. The mean esophageal transit time (52.56 ± 4.07 sec for patients; 24.30 ± 5.88 sec for controls; P=.02) and gastric emptying time (49.06 ± 4.29 min for the hypothyroid group; 30.4 ± 4.74 min for the control group; P=.01) were markedly increased in cases of hypothyroidism. Conclusion. Hypothyroidism prominently reduces esophageal and gastric motor activity and can cause gastrointestinal dysfunction.